2011
DOI: 10.1186/1476-511x-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase-1 protects against nutritional fibrosing steatohepatitis in mice

Abstract: BackgroundHeme oxygenase-1 (HO-1), an antioxidant defense enzyme, has been shown to protect against oxidant-induced liver injury. However, its role on liver fibrosis remains unclear. This study aims to elucidate the effect and the mechanism of HO-1 in nutritional fibrosing steatohepatitis in mice.MethodsMale C57BL/6J mice were fed with a methionine-choline deficient (MCD) diet for eight weeks to induce hepatic fibrosis. HO-1 chemical inducer (hemin), HO-1 chemical inhibitor zinc protoporphyrin IX (ZnPP-IX) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…Induction of HO-1 expression contributes to protection against liver damage in various liver diseases (36,37). We found that up-regulation of HO-1 could alleviate liver damage in BDL rats, which is in accordance with the findings of Barikbin et al In their study, induction of HO-1 interfered with chronic inflammation and prevented progression of liver fibrosis in Mdr2 knockout mice (36).…”
Section: Ho-1 Increased Occludin and Inhibited Phospho-nf-jb P65 Protsupporting
confidence: 90%
“…Induction of HO-1 expression contributes to protection against liver damage in various liver diseases (36,37). We found that up-regulation of HO-1 could alleviate liver damage in BDL rats, which is in accordance with the findings of Barikbin et al In their study, induction of HO-1 interfered with chronic inflammation and prevented progression of liver fibrosis in Mdr2 knockout mice (36).…”
Section: Ho-1 Increased Occludin and Inhibited Phospho-nf-jb P65 Protsupporting
confidence: 90%
“…HO-1, the rate-limiting enzyme in heme catabolism, has been reported to have potential antioxidant properties (Farombi and Surh, 2006). Previous studies have demonstrated the protective role of HO-1 in ameliorating MCD diet induced NASH (Wang et al, 2011;Nan et al, 2010). In addition, it was found that treatment with baicalein restored the activities of SOD and catalase, another two antioxidant enzymes, in livers of MCD fed rats.…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al, 139 Wang et al, 140 Velayudham et al Uchinami et al, 142 Buryova et al, 143 Popov et al, 144 Schrading et al, 145 Díaz-Gil et al, 146 Kossakowska et al 147 …”
Section: Metalloproteinases In the Development Of Liver Fibrosismentioning
confidence: 99%